Costa Rica Poverty Assessment : Recapturing Momentum for Poverty Reduction - World Bank (Washington, DC, 2012)
This study examines recent developments on the poverty front in Costa Rica, with particular emphasis on why poverty rates have not declined over the last 10 years despite consistent economic growth over the period. To accomplish this, the report develops a dynamic profile of poverty in Costa Rica to better understand the characteristics of the poor. It analyzes recent patterns of economic growth and the extent to which the poor have shared its benefits. The study also examines the dynamics of the labor market, including how recent labor market developments have affected the ability of the poor to generate higher incomes, particularly since 1994. It pays special attention to the impact that immigration from Nicaragua has had on poverty, and to the particular challenges faced by poor female workers. Finally, it examines the role and effectiveness of social sector spending and policies in improving the welfare of the poor and providing enabling them to escape poverty. The study is organized into three main parts. The first part of the report (chapters 1-4) focuses on the nature and evolution of poverty from 1989 to 2004. This includes presentation of a multi-dimensional profile of poverty (chapter 2), an analysis of the links between growth, income inequality and poverty reduction in Costa Rica (chapter 3), and an analysis of the role of the Costa Rican labor market in determining the earnings and opportunities faced by the poor (chapter 4). Part I1 (chapters 5-8) examines the role of the social sectors and social sector policies on poverty reduction in Costa Rica, focusing on education (chapter 6), health (chapter 7), and social protection (chapter 8). The final part of the report focuses on recapturing Costa Rica's momentum in reducing poverty. This part focuses first on strengthening economic and social policies to reduce poverty (chapter 9) and then on improving data for poverty monitoring and results-based management of Costa Rica's poverty reduction efforts.